Glandular odontogenic cyst: insights into a rare and challenging lesion - Schuch, Lauren Frenzel; Silveira, Felipe Martins; González Umpiérrez, Maria Natalia; Beovide-Cortegoso, Aurita Verónica; Pereira-Prado, Vanesa; Sicco, Estefanía; Bologna-Molina, Ronell (Journal of Oral Diagnosis, 2025)
The glandular odontogenic cyst (GOC) is a rare developmental odontogenic cyst characterized by an epithelial lining resembling salivary or glandular tissue. Its aggressive behavior and potential for recurrence pose challenges in both diagnosis and management. This review consolidates current knowledge on etiopathogenesis, clinical presentation, histopathological features, and treatment approaches. GOC primarily affects male adults, often presenting asymptomatically, and is most commonly found in the mandible. Radiographically, it appears as a unilocular or multilocular radiolucency, frequently associated with unerupted teeth. Histologically, GOC is distinguished by a multilocular cystic structure lined with epithelial cells, which may include “hobnail,” clear, and mucous cells. While traditionally thought to lack MAML2 gene rearrangements, recent studies have identified MAML2 fusion transcripts in recurrent GOCs, suggesting a link to aggressive behavior. The differential diagnosis includes both benign and malignant conditions. Treatment options range from conservative management to radical resection, with recurrence being a notable concern. This review highlights the need for accurate diagnosis and long-term follow-up, as no histopathological features reliably predict recurrence. Further research is needed to optimize treatment strategies and deepen understanding of its biological behavior.